Do stress and anxiety influence users' intention to make restaurant reservations through mobile apps? - Felipe Debasa; Vera Gelashvili; Juan-Gabriel Martínez-Navalón; José Ramón Saura (European Research on Management and Business Economics (ERMBE), 2023)
Today, people live in the age of new diseases, such as stress and anxiety, and these diseases can affect users' decision making regarding different products and services. Another important variable that can affect decision making is the use of mobile applications for marketing purposes. However, despite the importance of the aforementioned factors, relevant academic research on the impact of these variables on decision making has been scarce. The present study fills this gap in the literature using the technology acceptance model and integrating stress and anxiety variables. To this end, a sample of 672 customers of Spanish restaurants is analyzed. After carrying out a descriptive analysis of the sample and the variables, the structural equation model is used. In particular, the partial least squares model is used to test the hypotheses. The paper concludes with a discussion of how the results of the present study contribute to previous research on stress and anxiety, along with technology acceptance model variables, on decision making. In particular, the results have shown that there is no direct relationship between stress and perceived usefulness, and perceived ease of use, and attitude towards using. Although the relationship between stress and anxiety, perceived usefulness and attitude towards using, perceived usefulness and stress, and other relationships raised in the hypotheses have been confirmed.
Keywords: J50; J53; O32; M15; 650; Stress; Anxiety; Mobile apps; TAM model; PLS-SEM